EFEKTIVITAS MANAJEMEN KONSELING DALAM MENDISIPLINKAN PESERTA DIDIK KELAS 11 DI MA PERGURUAN MU’ALIMAT JOMBANG - Dimas Danuarta; Muhammad Al Fatih (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
Student discipline in school is very important to create an effective and productive educational environment. Good discipline helps reduce distractions in the classroom, ensures that students participate actively in learning, and creates a safe and comfortable school environment for them. Students face a variety of academic pressures, adolescent advancement, and more complex social demands, especially during 11th grade. This research has the objectives, (1) To find out how effective counseling management is at the MA Mu'alimat College in Jombang.(2) To find out how to discipline grade 11 students at the MA Mu'alimat Jombang College. (3) To find out how effective counseling management is in disciplining students at MA perguruan mu'alimat Jombang. This research uses a qualitative approach with a case study type of research. In obtaining data, researchers used observation, interview and documentation techniques, then the data obtained was analyzed using data reduction techniques, data presentation and drawing conclusions. The results of this research show that, (1) the counseling management carried out by MA Mualimat College is effective, in terms of planning the counseling guidance program, organizing counseling guidance, implementing the counseling guidance program, and supervising the counseling guidance program. The programs being run include; orientation programs, information service programs and individual counseling programs. (2) in disciplining students, MA Mu'alimat College establishes a system of violation points and reward points for female students who excel. (3) the effectiveness of counseling management in disciplining students starting from the process of planning counseling programs at meetings of teachers and madrasah staff, organizing the distribution of resources and cooperation between madrasah parties, implementing orientation counseling programs to individual counseling, and supervision carried out by madrasah principals and guidance counselors After an evaluation or meeting is carried out to assess the success of the program being implemented and whether it is in accordance with the goals and vision and mission of the madrasah, it can be said to be effective.